2022
DOI: 10.1371/journal.pone.0266108
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of antioxidant Avenanthramide-C on high-dose methotrexate-induced ototoxicity in mice

Abstract: Methotrexate (MTX) has been used in treating various types of cancers but can also cause damage to normal organs and cell types. Folinic acid (FA) is a well-known MTX antidote that protects against toxicity caused by the drug and has been used for decades. Since hearing loss caused by MTX treatment is not well studied, herein we aimed to investigate the efficiency of the antioxidant Avenanthramide-C (AVN-C) on high-dose MTX (HDMTX) toxicity in the ear and provide insights into the possible mechanism involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Most patients who were treated with known ototoxic cancer therapy received baseline hearing evaluations (i.e., cisplatin, carboplatin). Although MTX ototoxicity has been documented in mice, it is not a recognized ototoxic agent in humans ( Mateos et al, 2022 ; Umugire et al, 2022 ). Therefore, many of the patients with leukemia and osteosarcoma who were treated with MTX did not have baseline audiology exams.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients who were treated with known ototoxic cancer therapy received baseline hearing evaluations (i.e., cisplatin, carboplatin). Although MTX ototoxicity has been documented in mice, it is not a recognized ototoxic agent in humans ( Mateos et al, 2022 ; Umugire et al, 2022 ). Therefore, many of the patients with leukemia and osteosarcoma who were treated with MTX did not have baseline audiology exams.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Umugire et al (2022) demonstrated that MTX can cause severe hearing loss in mice by crossing the blood–labyrinth barrier and damaging neurons and OHCs of the cochlea. Furthermore, this group showed that the antioxidant Avenanthramide C created a strong protective effect against high-dose MTX-induced ototoxicity in mice and conserved the inner ear structures (synapses, neurons, and OHCs) from MTX-induced damage ( Umugire et al, 2022 ). Thus, further clinical, gene expression, molecular, and biochemical studies are warranted to determine its ototoxic and neurotoxic effects in humans and to develop appropriate therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation